Corroborating study on the absolute configurations of trigochinins A–C. Issue 50 (13th December 2017) - Fan, Yao-Yue; Chen, Shi-Xin; Liu, Qun-Fang; Gan, Li-She; Yue, Jian-Min
Graphical abstract: Highlights: Trigochinins A–C (1 –3 ) are three highly oxygenated daphnane-type diterpenes. The absolute configuration of1 was confirmed by X-ray crystallography study. The absolute configurations of2 and3 were confirmed by theoretical ECD study. Abstract: Trigochinins A–C (1 –3 ) are three highly oxygenated daphnane-type diterpenes isolated from Trigonostemon chinensis. Their structures with the absolute configurations were initially assigned by a combination of spectroscopic data, X-ray crystallography (Mo Kα radiation) study and CD analysis. In the current study, the absolute configurations of trigochinins A–C were confirmed by single crystal X-ray diffraction (Cu Kα radiation) study, CD spectral analogy, and theoretical ECD study by using quantum chemical TDDFT calculations.